PERAN KH. MA’MUN DALAM PERKEMBANGAN PONDOK PESANTREN RIYADLUL ‘ULUM WADDA’WAH TAHUN 1986-2014 M - Assondani, Mufti Najmul Umam; Arif, Nur (Jazirah: Jurnal Peradaban dan Kebudayaan, 2023)
Condong Islamic Boarding School was founded in 1984 AD by KH. Nawawi. The Condong Islamic Boarding School, which is also known today as Riyadlul 'Ulum Wadda'wah, originally had a traditional pesantren system until the leadership relay of KH. Ma'mun, the sixth generation. There has been development and renewal through the establishment of formal schools with an integrated system containing the salafiyah curriculum, the Pondok Modern Gontor curriculum and the Education Office curriculum. Therefore, the author wrote a study that aims to find out how the figure of KH. Ma'mun who was able to have a strong influence on the development of the Riyadlul 'Ulum Wadda'wah Islamic boarding school to continue to exist in the world of education and be able to compete in the era of globalization. The research method used is historical methodology with a focus on the historical approach used to find out how the biography of KH. Ma'mun starts from his life background until the process of his being elected as the leader of the pondok. With these steps, results were found which finally concluded that KH. Ma'mun played an important role in the development of the Riyadlul 'Ulum Wadda'wah Islamic Boarding School by adhering to the principles of المحُاَفَظَةُ عَلَى القَدِيْمِ الصَالِحِ وَالأَخْذُ باِلجَدِيْدِ الأَصْلَحِ (al-muhafadho tu 'ala qodimis sholih wal akhdzu bil bedil ashlah) namely maintaining good old traditions, and taking new things better.